Foxo‐mediated Bim transcription is dispensable for the apoptosis of hematopoietic cells that is mediated by this BH3‐only protein. (24th September 2013) - Herold, Marco J; Rohrbeck, Leona; Lang, Mathias J; Grumont, Raelene; Gerondakis, Steve; Tai, Lin; Bouillet, Philippe; Kaufmann, Thomas; Strasser, Andreas
Abstract : The BH3‐only protein Bim is a critical initiator of apoptosis in hematopoietic cells. Bim is upregulated in response to growth factor withdrawal and in vitro studies have implicated the transcription factor Foxo3a as a critical inducer. To test the importance of this regulation in vivo, we generated mice with mutated Foxo‐binding sites within the Bim promoters ( Bim ΔFoxo/ΔFoxo ). Contrary to Bim‐deficient mice, Bim ΔFoxo/ΔFoxo mice had a normal hematopoietic system. Moreover, cytokine‐dependent haematopoietic cells from Bim ΔFoxo/ΔFoxo and wt mice died at similar rates. These results indicate that regulation of Bim by Foxo transcription factors is not critical for the killing of hematopoietic cells. Abstract : Bim is crucial for initiating apoptosis and it had been suggested that its expression is regulated by Foxo3a. This report shows that in vivo, the regulation of Bim by Foxo transcription factors is not required for the killing of haematopoietic cells.